Plantando a cruz em chão de concreto: o cristianismo católico em contexto de metrópole a partir da Paróquia Nossa Senhora da Conceição do Tatuapé - Marchini, Welder Lancieri (2015)
The metropolitan constitution has significant impact on the religious life of its inhabitants. Starting from this statement, this work has as object the intersection between the metropolitan context and the parish religious experience having as locus of their study the parish Nossa Senhora da Conceição, at Tatuapé neighborhood in São Paulo. This research interprets the conditions of the metropolitan individual: their individuality, relationship with the institutions and their moral, describing the history and transformations of parish structures and analyzes the parish of Nossa Senhora da Conceição as a place where city and parish organization are mixed. Through field research, which followed a group of catechesis of adults in the same parish, it was found that religion metropolis context can only be understood against the background of a hybrid society. In response to the variety of metropolitan individuals, religion assumes characteristic of service, seeking to meet the most varied audiences, which hybridize in the parish environment